Molecular identification of the fungus Neurospora spp. isolated from Haematopinus tuberculatusfrom buffalo (Bubalus bubalis) - Ojeda-Robertos, Nadia Florencia; Aguilar-Marcelino, Liliana; Rodríguez-Vivas, Roger Iván; Sánchez-Cruz , Ricardo; Wong-Villarreal, Arnoldo (Ecosistemas y Recursos Agropecuarios, 2024)
The isolation of two fungal strains of the louse H. tuberculatus from water buffaloes raised in the tropics of Mexico is reported. Lice with the presence of abundant mycelium on their body were incubated for 12 h light/dark to promote mycelial growth. Fungi were transferred and isolated on potato dextrose agar medium (20%). From the two isolated strains, genomic DNA was extracted and the 28S rRNA genes and ITS sequences were amplified. The 76.1% of the lice collected showed white mycelium growth on their body. It was determined that the fungus belongs to the genus Neurospora spp. The present study allowed the discovery of the saprophytic fungus of the genus Neurospora in the louse H. tuberculatus, which was confirmed through its morphology and genetic sequencing.